RESPON ANAK DALAM MENGGUNAKAN APLIKASI TEKNOLOGI AKSARAGA BERBASIS ANDROID UNTUK PENINGKATAN PEMAHAMAN DAN AKSESIBILITAS BELAJAR AKSARA JAWA DI KOMUNITAS ANAK DUSUN SAREKAN, CANDEN, BANTUL - Dinar Westri Andini; Biya Ebi Praheto; Dyan Indah Purnama Sari (Universitas PGRI Yogyakarta, 2026)
Javanese script is one of the materials from the local content of the Javanese language that is often considered difficult to learn. Efforts are needed to help learn it through technology integration based on learning needs in the current digital era. The purpose of this service is to improve the understanding of children in the Canden Village area through the implementation of the Aksaraga application. The implementation method of this activity is carried out in 4 stages, namely socialization, mentoring, act & doing, and reflective & evaluation. This activity was carried out in the Sarekan Hamlet children's community which consists of 12 active member children at the elementary school level. The results of the implementation of this service activity provide an overview that through the implementation of the Aksaraga technology application, children can easily learn Javanese script, it is accessible, useful in helping understanding and interesting for children, so that this application can be one solution in making it easier to learn Javanese script in this digital era. Keywords: technology, Javanese script, aksaraga, android system, accessibility